PENGARUH PENGHINDARAN PAJAK DAN KEPEMILIKAN INSTITUSIONAL TERHADAP BIAYA UTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020 - Renika Hasibuan; Indah Purnamasari Aceh (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2022)
The aim of this research is to test about tax avoidance and institutional ownership towards cost of debts to manufacture firms in partial and simultaneously test registered to Bursary Effect of Indonesia (BEI) in 2016-2020. The research population is 193 companies. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period, totaling 193 companies. The number of samples used were 15 companies in 5 years of research as many as 75 companies using purposive sampling method. The data processing program uses SPSS (Staticical Product and Service Solution) version 25. The analytical method used in this study is the classical assumption test, multiple linear regression test, coefficient of determination test (R2), partial test (t-test) and simultaneous test (F test). The results of the study show that the variable tax avoidance has a positive and significant effect on the cost of debt while institutional ownership has a positive and significant effect on the cost of debt while tax evasion and institutional ownership simultaneously have a positive and significant effect on the cost of debt in companies listed on the IDX in 2016-2020.Keywords: Cost of Debt, Tax Avoidance and Institutional Ownerships.